Leadership Regeneration and Management Transformation as Strategic Approaches to Organizational Human Resource Development: A Case Study of AMA-Indonesia Batam - Heri Siswanto; Adelya Rifdah; Devina Wistiasari (Neo Journal of economy and social humanities, 2026)
This study analyzes leadership regeneration and management transformation as integrated strategic approaches to organizational human resource development (HRD) within a professional organization. Using a qualitative case study approach at AMA-Indonesia Batam, the research examines leadership succession not merely as a leadership change but as a strategic process that drives managerial transformation and human resource strengthening. Data were collected through in-depth interviews, observations, and document analysis involving organizational leaders, members, and the Muscab committee. The findings reveal that participatory and transparent leadership regeneration stimulates changes in organizational structure, decision-making processes, and work culture, which subsequently enhance member competence, organizational adaptability, and sustainability. Practically, this study provides guidance for professional organizations in designing participatory leadership succession mechanisms and adaptive management systems to support continuous HRD and long-term organizational sustainability. This study contributes analytical insights into the linkage between leadership succession and HRD in the context of local professional associations.